Evaluating the time of the visual scene and its relationship to the values of some biochemical variables in the performance of the main section of the spiking and blocking skills in the volleyball - Hasan, H. F.; Abdul, Y. D. B. (Journal of Human Sport & Exercise, 2021)
The biomechanical examination is worried about contemplating development and adds to expanding the degree of specialized players because of the utilization of present-day programming for kinematic investigation and the innovation of mechanical gadgets that have added to improve the specialized exhibition capacities of the players and the mentors follow the logical establishments in the improvement of execution strategies and assessment of the visual scene, and this visual kinematic measure in the divisions of a second expects us to Consider and assessing their planning and body development conditions in the fundamental segment of the two aptitudes and creating mathematical qualities that give an image of execution at these significant minutes as expected. The investigation meant to distinguish the assessment of the hour of the visual scene and its relationship with the estimations of some biochemical factors in the exhibition of the fundamental segment of the abilities to spike and impeding with volleyball. The exploration issue is the speed of development of the rival player and the ball and the trouble of focusing on it during self-survey by the mentor, explaining perspectives identified with centring consideration, knowing where the ball arrived from the stomach, the development of the player's arm, and picking the kind of hit or impeding the ball and its course. The two analysts utilized the spellbinding technique by the strategy for looking over on an example of the Iraqi public cooperative individuals for the year (2019-2020), and the main ends are that the player who plays out the of obstructing and pounding strikes and has an evaluation of the right visual scene can hit and repulse the ball because of the development of the arms and hands towards the ball well.